Diagnostic pathology : molecular oncology - Vasef, Mohammad; Auerbach, Aaron (Philadelphia, PA : Elsevier, 2016)
'Molecular Oncologic Pathology is one of the most dynamic fields of medicine and has become an intregral part of the field of pathology in particular. Introduction of massively parallel sequencing technology (aka next generation sequencing) in recent years resulted in discovery of several clinically actionable somatic mutations in solid tumors and in hematologic malignancies. These discoveries have refined our understanding of molecular pathogenesis of human diseases in general and have led to the discovery of many new molecular targeted therapies particularly in human cancers. Several of the recently discovered molecular genetic findings have already become critical for the diagnosis of distinct disease entities and key to personalized medicine. In oncologic pathology, these advancements have dramatically changed the role of the pure morphologic and immunophenotypic-based pathologist to that of a consultant who incorporates molecular genetic results into the pathology report and comprehensively interprets molecular data by creating an integrated report with the most clinically useful data in diagnostic line. Understanding new molecular information can be difficult for pathologists, clinicians, residents and medical students. This book is intended to serve as a guide for practicing pathologists, pathology residents and fellows to keep up with the rapidly evolving practice of pathology in era of personalized medicine. Diagnostic Pathology: Molecular Oncology is detailed, richly illustrated reference covering molecular tests and their clinical applications along with organ based chapters on the molecular genetic data relevant to individual disease entities. Focusing on accurate interpretation and diagnosis as well as molecular testing allows the creation of integrated reports that would guide oncologists in making proper treatment decisions. There is a scarcity of molecular pathology textbooks that are comprehensive, but easy to understand. Traditional textbooks are commonly paragraph-based with few photographs. In contrast, this book is extensively illustrated and written in a concise bulleted format, to allow the reader to easily find relevant information. The information covered in the text is cutting edge. Knowledge of the rapidly growing body of information regarding molecular pathology is essential to the understanding of modern day medicine. We hope that this textbook will be a valuable guide for this purpose. No book in the molecular genetic pathology can be considered complete given the dynamic nature of the field. Therefore, we invite the readers to share their thoughts and appreciate any feedback.'--Provided by publisher
Online access password (PDAL) : Y6ZRZ3UB26
Includes bibliographical references and index.
Keywords: Molecular diagnostic techniques -- Atlases; Pathology, molecular -- Atlases